21: DETERMINANTS OF VASCULAR INFLAMMATION BY 18-FLUORODEOXYGLUCOSE PET/MRI: FINDINGS FROM THE PSORIASIS, ATHEROSCLEROSIS AND CARDIOMETABOLIC DISEASE INITIATIVE. Issue 3 (23rd February 2016) - Kabbany, MT; Joshi, AA; Ahlman, M; Rodante, J; Lerman, JB; Aberra, T; Silverman, J; Dahiya, A; Bluemke, DA; Playford, MP; Mehta, NN
Abstract : Purpose of Study: Psoriasis (PSO), a chronic inflammatory disease associated with increased CV risk, provides a clinical human model to study inflammatory atherogenesis. We aimed to assess the major determinants of vascular inflammation (VI) measured by 18 FDG PET-MRI in a well-phenotyped PSO cohort. Methods Used: 124 consecutive patients with PSO underwent 18 FDG PET-MRI scans. We used target-to-background ratio to quantify VI 120 minutes post FDG injection. Homeostatic model assessment of insulin resistance (HOMA-IR) was measured, along with cholesterol efflux capacity (CEC) and HDL particle concentration by NMR (Liposcience) fasting. Summary of Results: Our cohort was middle aged (mean 49±13.3 years) with mild to moderate PSO, and low CV risk (median Framingham Risk Score (FRS) 2, IQR 2–6). PSO was associated with increased VI (β=0.27, p<0.005), compared to healthy controls. VI was associated with HOMA-IR (β=0.26, p<0.001), CEC (β=−0.12, p=0.04) and HDL particle concentration (β=−0.19, p=0.003) beyond traditional CV risk factors (age, gender, FRS and BMI). Among these, HOMA-IR provided maximum incremental value in predicting VI beyond traditional risk factors (χ 2 =39.36, p<0.001). Conclusions: VI by FDG PET MRI is associated with traditional CV risk factors and cardiometabolic parameters. Insulin resistance and CEC were most strongly associated with VI by 18 FDG PET-MRI beyond traditional CV risk factors and BMI in PSO suggesting that cardiometabolic disease increases CV risk in PSO.Abstract 21 Figure 1